Genital Tract Viral Load in HIV Type 1-Positive Women Correlates with Specific Cytokine Levels in Cervical-Vaginal Secretions But Is Not a Determinant of Infectious Virus or Anti-HIV Activity - Mukura, Lucy R. (Mary Ann Liebert, Inc., 2012)
As the AIDS epidemic continues with women being disproportionately affected, it is crucial to understand factors that predict the risk of heterosexual HIV-1 transmission. We investigated whether genital tract viral load (GTVL) in cervical-vaginal lavages (CVL) from HIV-1-positive women with moderately low CD4 T cell counts correlates with cytokine levels, antimicrobial concentrations, and intrinsic anti-HIV activity. CVL were collected from 19 HIV-1-positive women with moderately low CD4 T cell counts [mean 381 cells/mm(3) (227–536 cells/mm(3))]. None of the women was on antiretroviral therapy. The women were categorized into those with detectable GTVL or those with undetectable GTVL (detectable GTVL RNA levels > 400 copies/ml). Women were also categorized according to bacterial vaginosis (BV) status irrespective of GTVL. The TZM-bl assay was used to determine the presence of infectious virus and anti-HIV activity. Significantly higher levels of RANTES, Eotaxin, Fractalkine, IL-1α, IL-6, MCP-1, MIP1β, MIP1α, TNF-α, and GM-CSF were observed in women with detectable GTVL compared to women with undetectable GTVL. No significant differences were observed in the following cytokines and chemokines: G-CSF, IL-1RA, IL-8, and IP-10. GTVL did not correlate either with antimicrobials known to have anti-HIV activity or with the presence of infectious virus. BV status did not have a significant effect on anti-HIV activity. These findings further our understanding of the role of GTVL in determining the cytokine and chemokine milieu in the female reproductive tract.